The Role of University Incubators in Stimulating Entrepreneurial Education Activities and Sustainable Innovation in Morocco: A Critical Analysis - El Afqih, Brahim; Messaoudi, Abdelaziz (Journal of Education Culture and Society, 2025)
Aim. In recent years, interest in the role of university incubators has significantly increased in the Moroccan context. The study aims to analyse the role of university incubators and evaluate their contribution to entrepreneurial education activities and sustainable innovation within the Moroccan context.Methods. To achieve our aim, the study employs a qualitative methodology combining semi-structured interviews with 24 key actors in the Moroccan entrepreneurial ecosystem, thorough documentary analysis, and visits to six university incubators. This combined approach has enabled the development of a nuanced understanding of the university incubator ecosystem in Morocco.Results. Thematic analysis of the data revealed that, despite their crucial role as catalysts for entrepreneurial education, academic entrepreneurship, and sustainable innovation, the achievements of these incubators falls short of expectations. The study identifies several major challenges hindering the effectiveness of incubators, including lack of human resources, gaps in funding and support for entrepreneurs, and administrative and bureaucratic obstacles.Conclusion. Despite their potential, university incubators in Morocco face substantial challenges that hinder their contribution to entrepreneurial education activities and sustainable innovation. To enhance their effectiveness and promote sustainable entrepreneurial growth, it is essential to address funding gaps, improve human resource capacities, and streamline administrative processes. The results of this study offer valuable insights for university administrators, incubator managers, aspiring entrepreneurs, and stakeholders interested in fortifying Morocco’s entrepreneurial landscape. By implementing these insights, stakeholders can contribute to creating a more supportive environment for entrepreneurial education, sustainable innovation and economic development within the country.